Understanding the 2017 "Me Too" Movement's Timing. Issue 2 (May 2019) - Gibson, Camille; Davenport, Shannon; Fowler, Tina; Harris, Colette B.; Prudhomme, Melanie; Whiting, Serita; Simmons-Horton, Sherri
While persons may differ on the identified start of what evolved into the "Me Too" movement of 2017, the media focus makes the Anita Hill and Clarence Thomas saga of October 1991 a starting point for a slow cruise to a season of reckoning. This article explores the circumstances that led to a cataclysm where women have been believed and the alleged perpetrators have experienced consequences. These elements are a grassroots movement against sexual harassment across sectors; high-profile celebrity cases that attracted public attention; the use of a social media venue, the # MeToo, that facilitated the victims speaking publicly, from a safe distance from the harasser or abuser, no longer feeling compelled to silence for personal or career reasons; the election of a President (Trump) who was recorded jesting about engaging in sexual harassment; courageous investigative journalism in the face of threats from powerful persons; and President Obama's Title IX enhancements that put sexual assaults on college and universities in the news (and Betsy Devos's reversal of some of these initiatives). A final ingredient is the initial mistrial of Bill Cosby in 2017 (he has since been convicted of sexual assault in 2018).